2023
DOI: 10.21037/jtd-23-138
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of common and rare drug resistance patterns in Mycobacterium tuberculosis clinical isolates revealed by GenoType MTBDRplus and MTBDRsl assay

Zafran Khan,
Yuting Zhu,
Ping Guan
et al.

Abstract: Background Tuberculosis (TB) remains a significant global health emergency caused by Mycobacterium tuberculosis (Mtb). The epidemiology, transmission, genotypes, mutational patterns, and clinical consequences of TB have been extensively studied worldwide, however, there is a lack of information regarding the epidemiology and mutational patterns of Mtb in Pakistan, specifically concerning the prevalence of multi-drug resistant TB (MDR-TB). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…In China, the prevalence of MDR-TB was reported to be 34.85%. 46 A similar study in Ethiopia found a prevalence of MDR-TB to be 2% in the new cases and 15% in previously treated TB patients. 47 Our study, however, reported a 14-fold higher proportion of MDR-TB in new TB cases than what was reported in a systematic review and meta-analysis of multidrug-resistant tuberculosis in Ethiopian settings.…”
Section: Discussionmentioning
confidence: 90%
“…In China, the prevalence of MDR-TB was reported to be 34.85%. 46 A similar study in Ethiopia found a prevalence of MDR-TB to be 2% in the new cases and 15% in previously treated TB patients. 47 Our study, however, reported a 14-fold higher proportion of MDR-TB in new TB cases than what was reported in a systematic review and meta-analysis of multidrug-resistant tuberculosis in Ethiopian settings.…”
Section: Discussionmentioning
confidence: 90%